Composites Based on Polypropylene and Talc: Processing Procedure and Prediction Behavior by Using Mathematical Models - Laiza Marinho Racca; Elen Beatriz Acordi Vasques Pacheco; Luiz Carlos Bertolino; Cristiane Xavier da Silva Campos; Monica Calixto de Andrade; Ana Maria Furtado de Sousa; Ana Lúcia Nazareth da Silva (Advances in Condensed Matter Physics)
iPP/Talc composites were produced, with different methods of filler addition in iPP matrix. Two different grades of Talc were used for comparison. The tensile tests results showed that talc particles promoted an improvement in composite rigidity, indicating the reinforcing effect of the talc particles in the iPP matrix. However, PP/talc-based composites that were prepared from a masterbatch and with talc grade with smaller particle size showed a better efficiency on dispersion/distribution of particle filler on the thermoplastic matrix, resulting in an improvement in Young’s modulus property, even with higher filler contents. SEM analyses evaluated the composite morphologies and different mathematical models were used as a tool on prediction of mechanical behaviour of the materials. It was observed that the results of Young’s modulus of the composites can be adjusted by different models, depending on the talc characteristics and the mixing procedure used.